Research design : qualitative, quantitative, and mixed methods approaches - Creswell, John W. 4 0 16; 5 (Los Angeles : Sage, 2009)
Compares and contrasts qualitative, quantitative, and mixed methods of conducting research, and includes a glossary of terms, and research tips.
Includes bibliographical references and indexes.
Adult.
Keywords: 2 -- 0; 6; Research;Methodology.;Statistical methods. -- Social sciences;Social sciences;Social sciences; 20; 2